Fluoroquinolone Antibiotics and their Interactions in Agricultural Soils – A Review - Cláudio Ernesto Taveira Parente; Elcia Margareth Souza Brito; Antonio Azeredo; Rodrigo Ornellas Meire; Olaf Malm (Orbital: The Electronic Journal of Chemistry, 2019)
Fluoroquinolones (FQs) are antibiotics widely used in human and veterinary medicine. The main sources of FQ contamination in agricultural soils result from the irrigation of fields with wastewater and the use of waste sludge and animal manure as fertilizer. Due to their physicochemical properties, these chemicals exhibit strong sorption in soils, presenting low mobility, high persistence and, therefore, long-term biological action in this matrix. This review addresses their main physicochemical and biological interactions in soils, as well as their main biotic and abiotic degradation pathways. In addition, we highlight the possible impacts of FQs on organisms that play an important role in the maintenance of biogeochemical cycles such as soil microbiota, earthworms, and plants. Routes of exposure to human beings through food grown in contaminated soils, and possible exposure to resistant genes derived from microbiota-soil-antibiotic interactions are also discussed. This review emphasizes the need for establishing regulatory limits on FQ contamination sources through fertilization with human and husbandry waste in agriculture soils.DOI: http://dx.doi.org/10.17807/orbital.v11i1.1352